ORAN Architecture Strategy and Tactical Model Benchmarking Scenarios (Case Study: MNO Merger Impact Network Competition in Java Island) - Andi Oktarian; Muhamad Asvial (Syntax Literate, 2022)
The high level of population and penetration of data users in Indonesia and the number of similar products that have an impact on the tariff war, on the network or network side also has constraints on the limited frequency spectrum, difficulty in building networks or infrastructure with regional demographics that can only be penetrated with satellites or fiber optics, so that with this merger it will be able to increase synergy, growth and increase market position and profit. With the merger of several MNOs, it will certainly be a threat for large MNO-A operators in Indonesia to respond to it with war games from the network or network side to continue providing services with a good and maximum network both in terms of quality and coverage. The benchmarking method as one of the model systems in this paper provides a comprehensive comparison between MNO so that they can provide flexible, simplification and also efficient network solutions that MNO-A can do by applying ORAN technology so that it can accelerate the integration process both in terms of infrastructure to compete with a smart investment. Furthermore, with ORAN, MNO-A can take a more efficient strategy both with basic strategy, optimal strategy, and an aggressive strategy to maintain the pace of competition of all MNO in designing a network, opening up the digital divide and face competition from the impact of this merger, including (i) application carried out in urban areas with an overlay method and (ii) application in rural areas with extension or complement methods, with different levels of efficiency and complexity.